Shaping ability of three modern rotary instruments in simulated L-curved canals - Radwański, Mateusz; Łęski, Michał; Pawlicka, Halina (Journal of Stomatology, 2015)
Introduction. One of the challenges in endodontic therapy is preparation of highly curved canals. In everyday practice, stainless steel hand or NiTi mechanical instrumentation is used to achieve shaping procedure. A number of studies reported the superiority of rotary NiTi instruments over stainless steel hand files in root canal preparation. In the last decade, many types of rotary root canal instruments have been introduced. Aim of the study. To compare the shaping ability of three rotary instruments in simulated L-curved canals. Material and methods. In this experimental study, thirty resin blocks with simulated L-curved canals were used and randomly divided into three groups of ten blocks each. Canals were prepared to apical size 30 according to the recommendations of the manufacturer. Pre- and post-operative images were superimposed with GIMP 2.6 software. The amount of material removed from canal walls, changes of working length and apical transportation were measured and analyzed statistically. Results. Hyflex CM Files ensured more central apical preparation and maintained the original shape in this region as compared with other systems. On the other hand, the ProTaper Next instruments removed more resin from the coronal part, ensuring better conicity of this part of the canal with minimum deviation from the original course. In the present study, statistically significant higher difference of working length change was observed for ProTaper Next than Hyflex CM (p<0.05). Conclusion. The results of our research indicate comparable shaping abilities of the examined systems in L-curved resin blocks.